El Excentrico, 1958-04-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 5, 1958 [5 de abril de 1958]. Ano 8, No. 15. Cover contains a photo of a wedding in a church. It also serves as a flyer encouraging viewers to attend church on Easter Sunday.